2006
DOI: 10.1038/nature05159
|View full text |Cite
|
Sign up to set email alerts
|

Stem-cell ageing modified by the cyclin-dependent kinase inhibitor p16INK4a

Abstract: Stem-cell ageing is thought to contribute to altered tissue maintenance and repair. Older humans experience increased bone marrow failure and poorer haematologic tolerance of cytotoxic injury. Haematopoietic stem cells (HSCs) in older mice have decreased per-cell repopulating activity, self-renewal and homing abilities, myeloid skewing of differentiation, and increased apoptosis with stress. Here we report that the cyclin-dependent kinase inhibitor p16INK4a, the level of which was previously noted to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
766
2
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 989 publications
(824 citation statements)
references
References 33 publications
50
766
2
6
Order By: Relevance
“…16,132 Despite these findings (or perhaps due to this dysfunction) older mice have an increased number of HSCs, although these cells demonstrate reduced repopulating potential and a propensity towards myeloid skewing. 108,[133][134][135] Together, these findings strongly support the conclusion that aging expands one or more pools of dysfunctional HPCs/HSCs that limit the hematopoietic system response, especially in times of stress. Since DNA repair processes are disrupted with aging, DNA damage accumulates in the cells of older adults.…”
Section: Effects Of Aging On Hematopoietic Expressionsupporting
confidence: 65%
See 1 more Smart Citation
“…16,132 Despite these findings (or perhaps due to this dysfunction) older mice have an increased number of HSCs, although these cells demonstrate reduced repopulating potential and a propensity towards myeloid skewing. 108,[133][134][135] Together, these findings strongly support the conclusion that aging expands one or more pools of dysfunctional HPCs/HSCs that limit the hematopoietic system response, especially in times of stress. Since DNA repair processes are disrupted with aging, DNA damage accumulates in the cells of older adults.…”
Section: Effects Of Aging On Hematopoietic Expressionsupporting
confidence: 65%
“…154,155 However, numerous studies have found that CDKN2A expression increases in an age-dependent manner in most tissues, including the hematopoietic system. 133,156,157 TP53, another tumor suppressor gene, also displays a similar paradoxical expression pattern in aging and malignant transformation. Like CDKN2A, loss of TP53 activity promotes the development of hematopoietic malignancies, [158][159][160][161] and in mice, a "hyperactive" TP53 phenotype has been found to protect against cancer development.…”
Section: Effects Of Aging On Hematopoietic Expressionmentioning
confidence: 99%
“…Additionally, the p53/p21 pathway has been elucidated as a major regulator of aging. As tumour suppressor and cell cycle inhibitor, p16 is a marker of aging that accumulates in aged tissue (Janzen et al., 2006; Zindy, Quelle, Roussel, & Sherr, 1997). According to our study, both p53/p21 and p16 are activated in aged BMMSCs, which indicate that p53/p21 and p16 are involved in BMMSC aging.…”
Section: Discussionmentioning
confidence: 99%
“…The senescence biomarker p16 INK4a mediates cell cycle arrest through inhibition of cyclin‐dependent kinase 4 and 6 (CDK4/6), but p16 INK4a expression is not required for production of the SASP (Coppe et al., 2011). Furthermore, in vivo evidence suggests that the primary functional consequence of high p16 INK4a expression with aging is to limit the proliferation of specific cell types during homeostasis or in response to injury (Janzen et al., 2006; Krishnamurthy et al., 2006; Liu et al., 2011; Molofsky et al., 2006; Sousa‐Victor et al., 2014). Several groups, however, have suggested cell cycle independent effects of p16 INK4a and CDK4/6 inhibition (Goel et al., 2017; Murakami, Mizoguchi, Saito, Miyasaka & Kohsaka, 2012), and it is unclear whether reduced p16 INK4a expression can protect tissues from age‐related pathologies that are associated with the SASP but not with replicative failure.…”
Section: Introductionmentioning
confidence: 99%